Mellitate: A multivalent anion with extreme charge density causes rapid aggregation and misfolding of wild type lysozyme at neutral pH - Ścibisz, Grzegorz (PLoS One, 2017)
Due to its symmetric structure and abundance of carboxyl groups, mellitic acid (MA–benzenehexacarboxylic acid) has an uncommon capacity to form highly ordered molecular networks. Dissolved in water, MA dissociates to yield various mellitate anions with pronounced tendencies to form complexes with cations including protonated amines. Deprotonation of MA at physiological pH produces anions with high charge densities (MA(5-) and MA(6-)) whose influence on co-dissolved proteins has not been thoroughly studied. As electrostatic attraction between highly symmetric MA(6-) anions and positively charged low-symmetry globular proteins could lead to interesting self-assembly patterns we have chosen hen egg white lysozyme (HEWL), a basic stably folded globular protein as a cationic partner for mellitate anions to form such hypothetical nanostructures. Indeed, mixing of neutral HEWL and MA solutions does result in precipitation of electrostatic complexes with the stoichiometry dependent on pH. We have studied the self-assembly of HEWL-MA structures using vibrational spectroscopy (infrared absorption and Raman scattering), circular dichroism (CD), atomic force microscopy (AFM). Possible HEWL-MA(6-) molecular docking scenarios were analyzed using computational tools. Our results indicate that even at equimolar ratios (in respect to HEWL), MA(5-) and MA(6-) anions are capable of inducing misfolding and aggregation of the protein upon mild heating which results in non-native intermolecular beta-sheet appearing in the amide I’ region of the corresponding infrared spectra. The association process leads to aggregates with compacted morphologies entrapping mellitate anions. The capacity of extremely diluted mellitate anions (i.e. at sub-millimolar concentration range) to trigger aggregation of proteins is discussed in the context of mechanisms of misfolding.